Profil Kualitas Organoleptik Produk Segar Dan Matang Dari Ikan Nila (Oreochromis niloticus) Hasil Pengawetan Menggunakan Daun Keluwek (Pangium Edule Reinw.) - Candra, Krishna Purnawan; Hosana, Onedha; Yuliani, Yuliani; Emmawati, Aswita (Jurnal Pertanian Khairun, 2023)
Dayak tribe, as the native people of Kalimantan, has used the Keluwek plant for generations to prepare food sources of protein such as meat and fish. Apart from getting a preferred taste, this plant has also extended the food shelf life. This research aims to determine the sensory response profile of cooked products from preserved fish using Keluwek leaves. Tilapia fish is preserved using chopped Keluwek leaves for 2 days, then steamed and fried to get the cooked product. The organoleptic properties of fresh fish from preservation were compared with fresh fish without preservation using a quality assessment score of 1-9 based on SNI 01-2729.1-2006 for eyes, body surface mucus, odor, and texture. The cooked product's hedonic organoleptic properties and hedonic quality (color, aroma, taste and texture) were also observed (score 1-5). The results showed that on day 2 of preservation, the sensory properties of preserved fish were significantly different (p0.001) from fish without preservation for the eye, body surface mucus, smell, and texture attribute. Meanwhile, the sensory properties of the steamed cooked product are significantly different (p0.001) from those for the taste attribute but are not significantly different (p0.001) for the color, aroma, and texture attribute. Likewise, the sensory properties of the cooked fried product are significantly different (p0.001) for the color, aroma, taste and texture attribute. The steamed cooked product of preserved tilapia received a neutral response. for the attribute of color, aroma, taste, and texture. Meanwhile, the cooked fried product of preserved tilapia received a bit dislike response for the attribute of color, smell, taste, and a neutral response to texture attribute.Keywords: Keluwek, Nile fish, fish preservation.